The Charter and General Ordinances of the Town of Lexington, Virginia Page 87, Image 107 (1892) - (:unkn) unknown (My University, 1869)
If any person sell, barter, give or furnish, or cause to be sold, bartered, given or furnished to any minor under sixteen years of age, cigarettes, or pistols, or dirks, or bowie knives, having good cause to believe him or her to be a minor under sixteen years of age, shall be fined not less than ten dollars nor more than one hundred dollars."
Keywords: TRANSFER - MINORS